Study on Nanoglue Bonding Technology of State Equation Experimental Target - CHEN Guo;ZHANG Ling;HUANG Jinglin;LIU Yansong;WANG Tao;AI Xing;LI Jun;HE Xiaoshan (Yuanzineng kexue jishu, 2023)
Laser loading compression is one of the main research topics in the field of inertial confinement fusion. In order to simulate and explain the experimental phenomena of materials under high strain rates and pressures generated by laser shock, the submicron requirements for the adhesive layer thickness between the target multilayer materials in the state equation experiment were proposed in the physical experiments. Compared with the existing recombination methods, a novel adhesive recombination was reported in this paper. The poly glycidyl methacrylate (pGMA) film was prepared by initiating chemical vapor deposition method, and the liquid phase activation method was used to activate and cure the solid adhesive film. The submicron lossless bonding recombination of the state equation test target could be realized. In the activation process of pGMA film, the liquid phase activation method proposed in this paper will greatly improve the connection strength of multilayer materials without changing the thickness of the adhesive layer, which has not been reported. The thickness and morphology of the pGMA film were characterized, and the influence of process parameters on the film thickness was discussed. The deposition rate of pGMA film is about 10 nm/min in this paper. The white light confocal technology was used to indirectly measure the adhesive layer thickness of some nanoglue bonding samples. For the materials such as hydrocarbon and high-density carbon, the adhesive layer section of the nanoglue bonding samples was prepared by means of metallographic sample preparation combined with ion beam etching, and the adhesive layer thickness was directly characterized by scanning electron microscopy. The above results show that the adhesive layer thickness of the nanoglue bonding samples is submicron. And the thinnest adhesive layer of the nanoglue bonding samples is only 300 nm. The morphology of adhesive layer about the nanoglue bonding samples was characterized by optical microscope. The nanoadhesive layer connected the multilayer materials together evenly and seamlessly, and there were no gaps and air bubbles between the samples. The nanoglue bonding method reported in this paper has many advantages, such as precise control of the adhesive layer thickness, greatly improving the connection strength between the multilayer samples of the target in the equation of state experiment, realizing the precise assembly of the target with small size and complex configuration. This method will provide technical support for the improvement of the precision of laser loading compression physical experiment and the accurate interpretation of experimental results.